Differentiated instruction using slow-motion video and task cards to enhance critical thinking in elementary physical education - Dini Aji Permatasari; Advendi Kristiyandaru; Mochamad Ridwan (Sriwijaya Journal of Sport, 2026)
Research Background: The development of critical thinking skills is a central goal of 21st-century education and is emphasized in Indonesia’s Independent Curriculum. However, Physical Education (PE) in many elementary schools remains teacher-centred, limiting students’ opportunities for higher-order thinking. Research Objectives: This study examines the effectiveness of differentiated instruction integrated with slow-motion video and task cards in enhancing students’ critical thinking skills in Physical Education. Methods: A quasi-experimental pretest–posttest control group design was employed, involving 46 fifth-grade students selected through cluster random sampling. Participants were assigned to experimental and control groups. Critical thinking was measured using a validated 17-item questionnaire. The intervention, conducted over four sessions, combined slow-motion video analysis of basic basketball movements with differentiated task cards tailored to students’ readiness levels. Results: Results indicated a significant improvement in the experimental group (67.87 to 78.39) compared to the control group (68.78 to 71.13). Statistical analysis showed a significant difference (p < 0.05) with a large effect size (Cohen’s d ≈ 1.27). Conclusion: These findings suggest that integrating visual media with differentiated tasks effectively promotes student-centred learning and enhances critical thinking in PE.